Security wireless sensor networks: prospects, challenges, and future - Pathan, Al-Sakib Khan (Kyung Hee University, South Korea, 2008)
With the advancements of networking technologies and miniaturization of electronic devices, wireless sensor network (WSN) has become an emerging area of research in academic, industrial, and defense sectors. Different types of sensing technologies combined with processing power and wireless communication capability make sensor networks very lucrative for their abundant use in near future. However, many issues are yet to be solved before their full-scale practical implementations. Among all the research issues in WSN, security is one of the most challenging topics to deal with. The major hurdle of securing a WSN is imposed by the limited resources of the sensors participating in the network. Again, the reliance on wireless communication technology opens the door for various types of security threats and attacks. Considering the special features of this type of network, in this chapter we address the critical security issues in wireless sensor networks. We talk about cryptography, steganography, and other basics of network security and their applicability in WSN. We explore various types of threats and attacks against wireless sensor networks, possible countermeasures, mentionable works done so far, other research issues, etc. We also introduce the view of holistic security and future trends towards research in wireless sensor network security.